Strategi Pemasaran Air Mineral dalam Kemasan pada PT Viura Indo Tirta, Bogor Menggunakan Metode Analisis SWOT - Syamruddin Syamruddin; Gin Gin Ginanjar (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2026)
The objective of this study is to assess the internal and external conditions of PT Viura Indo Tirta, Bogor by identifying its strengths, weaknesses, opportunities, and threats, thereby enabling the formulation of an appropriate marketing strategy using SWOT analysis. The study employs a mixed-methods approach. Data analysis techniques include SWOT analysis, IFE Matrix analysis, EFE Matrix analysis, IE Matrix analysis, the SWOT Matrix, and the SWOT analysis diagram. Results from the IFE Matrix indicate a total score of 3.07 for strengths and weaknesses, while the EFE Matrix shows a total score of 3.20 for opportunities and threats. The IE Matrix places the company in Cell I (Strong), indicating that a